Local Government Communication Strategy in Resolving Religious Building Conflicts in Aceh - Sarkawi, Sarkawi; Sazali, Hasan; Khatibah, Khatibah (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
Conflicts over the establishment of houses of worship in Indonesia continue to recur despite the government having established regulations such as PBM 2006 and Law No. 7/2012. This shows a gap between the legal framework and the government's communication capabilities in managing interfaith relations. This study aims to analyze the dynamics of conflicts over the establishment of houses of worship in Aceh Singkil and assess the effectiveness of government communication strategies within the framework of conflict communication theory and Islamic communication principles. The research method employs a qualitative descriptive approach, utilizing in-depth interviews with local government officials, religious leaders, and community leaders, as well as an analysis of regulatory documents. The findings show that the conflict in Aceh Singkil is administrative in nature and rooted in the mismatch between regulatory requirements and the actual needs of the community. The government's communication strategy is multidimensional, combining regulation, interfaith dialogue, and persuasive da'wah principles; however, it does not yet fully involve traditional actors who hold high social legitimacy. As a result, government communication has been effective in reducing short-term tensions but has not been able to produce long-term solutions. This study emphasizes the importance of a holistic and collaborative communication approach that involves traditional stakeholders as a sustainable strategy in religious conflict resolution.